Katekese Kontekstual sebagai Respons Pastoral terhadap Tantangan Budaya Populer dalam Pendidikan Iman Anak dan Remaja Katolik - Yongki Saputra; Yoseph Lamuji; Ebandro Ebandro; Silfester Oktovius Rewak Hipir; Felisitas Yuswanto (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
Popular culture and digitalization have become the main context of the lives of Catholic children and adolescents, thus having a significant impact on the formation of their identity, values, and practices of faith. Phenomena such as social media, music, movies, and digital games are not only entertainment spaces, but also pedagogical spaces that shape the way of thinking and spirituality of the younger generation. This study aims to analyze the relevance of Thomas H. Groome's Shared Christian Praxis (SCP) model as a contextual catechesis approach for children and adolescents living in popular culture. Using a qualitative method based on literature studies, this study interprets popular cultural dynamics, the principles of the Church's faith education, and the SCP approach through hermeneutical and thematic analysis. The results show that traditional catechesis approaches are no longer adequate to answer the needs of the digital generation which demands a dialogical, participatory, and experiential learning process. The SCP approach has been proven to be able to integrate students' experiences, critical reflection, the Church's story of faith, hermeneutical dialogue, and concrete actions as a single faith-building process. Thus, this research makes a practical contribution to the Church and Catholic educational institutions in designing catechesis strategies that are more relevant, contextual, and able to respond to the challenges of popular culture faced by the younger generation.